Editorial: Instruments and practices for Open Science in Criminal Procedure - perplexities and some possibilities - Bruna Capparelli; Nereu José Giacomolli (Revista Brasileira de Direito Processual Penal)
The present editorial draws a reflection on the intersections and overlaps of notions and interpretations of the concept of scientific assignment, open data and open science in Criminal Procedure. Based on the premise that the public disclosure of data and statistics in open access represents both a guarantee regarding the quality and seriousness of the information, and an economy of time and resources for scientific research, this editorial is focused on the criteria for willingness of the scientific community to validate the research.